Research antology on bussiness continuity and navigating time of crisis - Sánchez Flores, Rebeca; Cruz-Sotelo, Samantha; Ojeda-Benitez, Sara; Navarro González, Carlos (IGI Global, 2022)
The purpose of this chapter is to present an overview of current research on sustainable procurement identifying practices and case studies in supply chain that have been said to improve its performance from a global perspective. As an introduction, this chapter describes the importance of sustainability in supply chain, driving the discussion into the procurement process. Theoretical perspectives used in sustainable supply chain literature are presented, focusing on procurement management and the three dimensions of sustainability. The chapter discusses current procurement practices as a source of competitive advantage. It also highlights techniques, tools, and methodologies from research case studies, and presents sustainable procurement practices as a driver of performance improvement. Finally, this chapter provides further research directions and confirms sustainable procurement as a key process to performance enhancement in supply chain management, and as a source for global business improvement and competitive advantage achievement.
Sustainable procurement to enhance organizational performance in supply chain management: current research and practices
Keywords: Sustainability; Procurement; Organizational Performance; Supply Chain; Sustainable Practices; Supply chain management; Campus Mexicali